1996
DOI: 10.1136/bmj.312.7031.604
|View full text |Cite
|
Sign up to set email alerts
|

Thunderstorm associated asthma: a detailed analysis of environmental factors

Abstract: New episodes of asthma during the epidemic on 24 and 25 June 1994 were associated with a fall in air temperature and a rise in grass pollen concentration. Non-epidemic asthma was significantly associated with a greater number of environmental changes. This may indicate that the patients with thunderstorm associated asthma were a separate population, sensitive to different environmental stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
119
2
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(135 citation statements)
references
References 16 publications
(23 reference statements)
9
119
2
5
Order By: Relevance
“…The data are consistent with previous investigations of thunderstorm asthma epidemics in London, Melbourne, and Tamworth [2,4,10]. Allergy to rye grass pollen and history of hayfever has been associated with thunderstorm asthma exacerbation in previous investigations [2,4,13]. This is consistent with the findings of the current study in which 95% of thunderstorm cases were allergic to rye grass and a similar proportion reported prior hayfever symptoms.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The data are consistent with previous investigations of thunderstorm asthma epidemics in London, Melbourne, and Tamworth [2,4,10]. Allergy to rye grass pollen and history of hayfever has been associated with thunderstorm asthma exacerbation in previous investigations [2,4,13]. This is consistent with the findings of the current study in which 95% of thunderstorm cases were allergic to rye grass and a similar proportion reported prior hayfever symptoms.…”
Section: Discussionsupporting
confidence: 83%
“…However, it is anticipated that most patients with asthma in Wagga Wagga would use the emergency department service for acute episodes. The data are consistent with previous investigations of thunderstorm asthma epidemics in London, Melbourne, and Tamworth [2,4,10]. Allergy to rye grass pollen and history of hayfever has been associated with thunderstorm asthma exacerbation in previous investigations [2,4,13].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Possible precipitating factors are the commencement of the new school year, with the rapid transmission of a virus predisposing to asthma attacks, 3,4 high levels of grass pollen resulting from high summer rainfalls, or other environmental causes related to meteorological conditions. 5,6 Localised factors, such as air pollution, or industrial contaminants, 7 are not likely to be implicated, as children were affected over a large area of the state. The northern-and southern-most boundaries of the outbreak have not yet been defined.…”
Section: Discussionmentioning
confidence: 99%
“…The seasonal causes of the increases in asthma have been explained in terms of meteorological and pollutant variables. Regarding the meteorological variables, different authors have concluded that the symptoms may be related to the temperature prevailing during cold periods (Beer et al, 1991;Yuksel et al, 1996), changes in temperature (Crighton et al, 2001), relative humidity and rainfall (Celenza et al, 1996), fog (Kashiwabara et al, 2002), wind speed (Hashimoto et al, 2004), and changes in barometric pressure and storms (Sutherland and Hall, 1994;Newson et al, 1997).…”
Section: Introductionmentioning
confidence: 99%